Medical embryology and regenerative medicine: research and applications in clinical practice - Soczyńska, Julia; Gawełczyk, Wiktor; Obrycka, Patrycja; Żołyniak, Mateusz; Muzyka, Adrian; Majcherczyk, Krzysztof; Papierkowska, Julia; Woźniak, Sławomir (Frontiers in Cell and Developmental Biology, 2025)
Medical embryology, as a discipline focused on the developmental processes of living organisms, constitutes the foundation of regenerative medicine through its close integration with genetics, engineering methodologies, and biotechnology, particularly in the field of stem cell cultivation. Investigating its fundamental pillars, such as epigenetics, biomaterials, and bioreactors, within an interdisciplinary framework, is essential for the advancement of modern precision medicine. A thorough understanding of cellular-level processes is undoubtedly the basis for major scientific breakthroughs. Detailed research on the influence of microenvironmental factors on the future function of stem cells, including artificial modulation of external signals that mimic in vivo conditions -such as chemical gradients or specific pathways like Notch and Hedgehog -has enabled effective regulation of cellular behavior. Combined with the potential of biotechnology, these advancements open new perspectives for disease treatment and organ regeneration. Taking this progress a step further, the ability to introduce stem cells into damaged tissues, thereby facilitating the formation of functional structures, has led to the growing interest in organoids -three-dimensional models that replicate key functions of real organs. Organoids are currently applied not only in drug screening but are also gaining increasing attention for their role in cancer therapy research. This technology holds the potential to revolutionize medicine, although significant challenges remain, particularly in standardizing cell culture conditions and achieving adequate vascularization of organoid structures. Many advanced regenerative technologies, such as gene editing and bioprinting, are additionally associated with high costs, logistical limitations, and uncertain outcome predictability. Efforts are underway to translate these therapies into clinical practice and to analyze treatment efficacy under real-world conditions, especially in cases where conventional medical approaches prove insufficient. Solving these challenges would mark a scientific breakthrough comparable to the promising results observed in personalized medicine approaches that significantly improve patients’ quality of life. Inspired by the potential of applying modern technologies within an interdisciplinary context, we undertake a comprehensive literature review exploring the integration of embryology and regenerative medicine. We also encourage reflection by addressing the ethical considerations associated with these developments, balancing moral responsibility with legal frameworks.